Playfair with Multi Strata Encryption - Salih, Raghad K.; Yousif, Madeha Sh. (Iraqi Journal of Science, 2021)
Playfair cipher is a substitution scheme. The classical playfair scheme has a limited matrix size containing only uppercase letters, so it is prone to hackers and cryptanalysis. To increase the resistance of playfair cipher, a new encipherment and decipherment method is proposed in this work, which depends on the permutation and its inverse, respectively. In addition, a modified key matrix is utilized, which includes capital and small Alphabets, numbers, and 38 special characters collected from ASCII codes. In the proposed method, both substitution and transposition schemes are used, where the first stratum of the cipher is a substitution by using key matrix and the second stratum is a transposition by using permutation key which provides multi strata resistance to brute force and other cryptanalysis attacks. A comparison between the traditional playfair scheme and the proposed method demonstrates that the encoded text is hard to recognize by cryptanalysts, which improves the security of the encryption process.